Socio-demographic factors and cultural beliefs in early child weaning among mothers of Onigbongbo community, Lagos State, Nigeria - Rapheal Kehinde Falegbe; VE ADAMU (Orapuh, Inc., 2023)
Introduction Weaning is the introduction of supplementary food into a child's diet after the first six months of life. Early introduction of the food and incorrect weaning practices are commonly found among mothers around the world. Purpose This research work was designed to assess the socio-demographic and cultural factors influencing maternal decision on early child weaning. Material and methods The study was of a cross-sectional survey research design. Data was collected with the aid of a questionnaire that was designed to elicit the desired responses. 394 mothers selected from the 39,385 women (using the Yaro Yemane formula) that attended the Immunisation Plus Day (IPD) of the Primary Health Care (PHC) Centre located at the Onigbongbo community in Lagos State, Nigeria were given the questionnaires to fill out but only 251 returned them because the research was conducted at the height of the COVID-19 pandemic (63.71% return rate). Data got from this exercise were analysed using Statistical Package for Social Sciences (SPSS), version 25, at a 95% confidence level and 0.05 marginal error. Result Results indicated that there was a positive relationship between early child weaning and maternal age (r .040 and p-value of .525), educational level (r .093 and p-value of .142), and income level (r .160 and p-value of .011). On the other hand, there was a negative relationship between early child weaning and the belief that breast milk is insufficient for the baby (r = -.015 and p-value of .807), child ill-health results from exclusive breastfeeding (r -.090 and p-value .153), complementary feeding is more nutritious than breast milk (r -.050 and p-value .431), and continuous breastfeeding causes breast sagging (r -.025 and p-value .688). Conclusion A significant relationship exists between predisposing factors and early child weaning practices among the mothers owing to their level of income, educational status, age, income, and cultural beliefs and practices.